Maternal feeding practices and toddlers' fruit and vegetable consumption: results from the DIT-Coombe Hospital birth cohort in Ireland. - Liu, Xiyao; Zhou, Qianling; Clarke, Keara; Younger, Katherine M.; An, Meijing; Li, Zhouyinuo; Tan, Yang; Kearney, John M. (Nutrition Journal, 2021)
Background: Health benefits of fruit and vegetable have been well recognized. However, insufficient consumption of fruit and vegetable is prevalent among toddlers, and has become a global public health issue. Maternal feeding practices are potential factors influencing toddlers' dietary intake, including fruit and vegetable intake. This study was conducted to explore the influence of maternal feeding practices on toddlers' fruit and vegetable consumption in Ireland.Methods: A follow-up to the DIT-Coombe Hospital birth cohort was conducted. Mothers in the original cohort were invited to participate in the present follow-up study by phone. A questionnaire assessing maternal feeding behavior and the child's 3-day food diary was sent to mothers who agreed to take part in the present study by post, together with a self-addressed stamped envelope.Results: There were 193 mother-children pairs included in the analysis, and the mean age of children was 2.4 (SD 0.7) years old. Toddlers' mean daily intakes of vegetable and fruit were 67.57 (SD 45.95) g and 213.35 (SD 170.78) g, respectively. Logistic regression analyses showed that maternal practice of breastfeeding for more than 4 weeks was positively associated with fruit (OR = 2.93, 95% CI: 1.29-6.64) and vegetable (OR = 1.95, 95% CI: 1.00-3.81) intake or the contribution of fruit (OR = 2.62, 95% CI: 1.19-5.80) and vegetable (OR = 2.02, 95% CI: 1.02-3.99) to the total diet. Letting the child eat with other family members was associated with high vegetable intake (OR = 5.45, 95%CI: 1.69-17.61) and high contribution of vegetable to total diet (OR = 3.78, 95% CI: 1.04-13.82). Not being too worried about the child's refusal to eat was positively associated with toddlers' vegetable intake (OR = 2.10, 95%CI: 1.09-4.05).Conclusions: To increase children's fruit and vegetable intake, and develop good eating habits, parents should eat with their toddlers, be patient and not put much pressure on their children in the context of meal feeding.